Chinese mothers as allies of patriarchy in Amy Tan’s The Joy Luck Club - Benarioua, Amira (AMERICANA E-journal of American Studies in Hungary, 2018)
In the present paper, I aim to investigate the concept of motherhood and its role in reinforcing male sexist stereotypes in the Chinese-American novel The Joy Luck Club (1989). The paper explores the controversial nature of motherhood and its implications on the psychological well-being of both the mother and daughter. Moreover, the paper displays the ambivalent role Chinese mothers play in the lives of their American born daughters and demonstrates the different factors and circumstances that affect the mothers’ behavior with their daughters. In China, the mother proves to be an oppressive force, an agent that along with the man works to enforce women’s inferiority and subordination.